2009
DOI: 10.1519/jsc.0b013e3181b3e1b6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Speed of Squat Movement and the Use of Accommodated Resistance Among College Athletes Training for Power

Abstract: The purpose of this study was to assess the effect of heavy/slow movements and variable resistance training on peak power and strength development. Forty-eight National Collegiate Athletic Association (NCAA) Division I athletes (age: 21.4 +/- 2.1 years, all men) were recruited for this 12-week training intervention study. Maximum strength and jumping power were assessed before and after the training program. Athletes were randomly assigned to 1 of 3 training groups: heavy resistance/slow movement (Slow), light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 6 publications
5
50
2
4
Order By: Relevance
“…The majority of longitudinal studies that have investigated the effects of combining variable resistance material with freeweights have used rubber bands (2,13,19,21,35). The results have clearly demonstrated that the addition of rubber bands can significantly improve measures of strength and power and those improvements are generally significantly larger than those achieved when using a constant resistance (2,13,35). However, on the basis of the mechanical differences highlighted in the present study it would be inappropriate to generalize the more positive results obtained for rubber bands to the use of chain resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of longitudinal studies that have investigated the effects of combining variable resistance material with freeweights have used rubber bands (2,13,19,21,35). The results have clearly demonstrated that the addition of rubber bands can significantly improve measures of strength and power and those improvements are generally significantly larger than those achieved when using a constant resistance (2,13,35). However, on the basis of the mechanical differences highlighted in the present study it would be inappropriate to generalize the more positive results obtained for rubber bands to the use of chain resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This causes the load to increase as the lifter rises during the concentric action and can be more explosive (McMaster, T., Cronin, J., McGuigan, 2009). Rhea (Rhea, Kenn, & Dermody, 2009) found that the use of bands with fast movements increased peak power greater than slow heavy movements yet both similarly increased maximal strength. The current study also demonstrated that variable resistance increased strength.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown to increase force, strength, and power of the upper (Ghigiarelli, Nagle, Gross, Robertson, Irrgang, & Myslinski, 2009) and lower body (Israetel, McBride, Nuzzo, Skinner, & Dayne, 2010;Rhea, Kenn, & Dermody, 2009;Wallace, Winchester, & McGuigan, 2006 ). However, limited research has examined short-term variable resistance training to specifically increase jump height.…”
Section: Introductionmentioning
confidence: 99%
“…Both types of accommodating resistance are commonly recommended in powerlifting training for ''overloading the top of the range of motion'' (Neelly et al 2010c;Rhea et al 2009) or increasing the rate of force development Baker and Newton 2009;Anderson et al 2008;Neeld 2010) in a lift such as the squat, the bench press or the deadlift. However, despite their widespread use, they are poorly understood and are generally applied in an ad hoc manner.…”
Section: Accommodating Resistancementioning
confidence: 99%